Optimizing Turbo Code Performance: Analyzing the Impact of Free Distance - Sabriya Alghennai Salheen; Najat Abohamra; Abdussalam Ali Ahmed (African Journal of Advanced Pure and Applied Sciences, 2024)
The performance of Turbo codes, a robust error correction method, is influenced by various factors. This study specifically explores the pivotal role of free distance in Turbo code performance, a crucial parameter defining error correction capabilities. Employing an extensive simulation framework encompassing realistic channel models and decoding algorithms, we scrutinize the impact of varied free distance values on Turbo codes’ overall efficacy. Our investigation spans a spectrum of free distance values, evaluating their influence on both bit error rate (BER) and frame error rate (FER) metrics across additive white Gaussian noise (AWGN) and fading channels, mirroring practical communication scenarios. The outcomes underscore a clear correlation: augmenting free distance enhances error correction, lowering BER and FER. Yet, this improvement incurs escalated decoding complexity, necessitating more iterations for higher free distance values. Additionally, we delve into diverse interleaver designs’ effects on Turbo code performance across varying free distances. Our findings illuminate certain interleaver configurations that enhance error correction capacities, even with lower free distance values. This emphasizes the significance of optimizing interleaver design to bolster performance under specific channel conditions. This study offers crucial insights into how free distance influences Turbo code performance, elucidating the trade-off between error correction capabilities and decoding complexity. These insights empower researchers and engineers to make informed decisions while designing and implementing Turbo codes in real-world communication systems.